Mitochondrial Calcium Overload Plays a Causal Role in Oxidative Stress in the Failing Heart - Haikel Dridi; Gaetano Santulli; Laith Bahlouli; Marco C. Miotto; Gunnar Weninger; Andrew R. Marks (Biomolecules, 2023)
Heart failure is a serious global health challenge, affecting more than 6.2 million people in the United States and is projected to reach over 8 million by 2030. Independent of etiology, failing hearts share common features, including defective calcium (Ca2+) handling, mitochondrial Ca2+ overload, and oxidative stress. In cardiomyocytes, Ca2+ not only regulates excitation–contraction coupling, but also mitochondrial metabolism and oxidative stress signaling, thereby controlling the function and actual destiny of the cell. Understanding the mechanisms of mitochondrial Ca2+ uptake and the molecular pathways involved in the regulation of increased mitochondrial Ca2+ influx is an ongoing challenge in order to identify novel therapeutic targets to alleviate the burden of heart failure. In this review, we discuss the mechanisms underlying altered mitochondrial Ca2+ handling in heart failure and the potential therapeutic strategies.